Labral Reconstruction: When to Perform and How - White, Brian J.; Herzog, Mackenzie M. (Frontiers in Surgery, 2015)
Over the past decade, the understanding of the anatomy and function of the hip joint has continuously evolved, and surgical treatment options for the hip have significantly progressed. Originally, surgical treatment of the hip primarily involved resection of damaged tissue. Procedures that maintain and preserve proper hip anatomy, such as labral repair and femoroacetabular impingement (FAI) correction, have shown superior results, in terms of pain reduction, increased function, and ability to return to activities. Labral reconstruction is a treatment option that uses a graft to reconstruct the native labrum. The technique and outcomes of labral reconstruction have been described relatively recently, and labral reconstruction is a cutting edge procedure that has shown promising early outcomes. The aim of this article is to review the current literature on hip labral reconstruction. We will review the indications for labral reconstruction, surgical technique and graft options, and surgical outcomes that have been described to date. Labral reconstruction provides an alternative treatment option for challenging intra-articular hip problems. Labral reconstruction restores the original anatomy of the hip and has the potential to preserve the longevity of the hip joint. This technique is an important tool in the orthopaedic surgeon’s arsenal for hip joint treatment and preservation.